Training on creating learning media for handling of disaster mitigation for elementary school teachers - Rachman, Indriyani; Murae, Fumitoshi; Kodama, Yayoi (ASEAN Natural Disaster Mitigation and Education Journal, 2024)
Background: Indonesia is known as a disaster-prone country, the total amount of damage due to disasters is said to be the fourth largest in the world. The impact of global warming results in very high rainfall and large-scale damage. Apart from weather disasters, a number of damages also occur due to geological disasters. To stop disaster damage in the long term, it is important to create sustainable communities. It is important not to separate the environment and disaster prevention, but to learn about the nature that sometimes threatens us just as we learn about the nature around us. Under these conditions, until now Indonesia has not included practical disaster education in the learning curriculum, because it is considered important to include disaster management training in school communities. Because of this, disaster management methods were tested in Japan, tested in elementary schools in the city of Mataram, Indonesia. This research aims to evaluate whether adapting traditional Japanese educational methods such as "exploring the environment (Machitanken)" and "picture story performances (Kamishibai)", and presentations (hapyoukai) are adapted to local conditions. existing policies in Indonesia, can be applied in Indonesia. Methods: This research was conducted in the city of Mataram, carried out for one year via Zoom, involving 7 elementary school teachers, one middle school teacher, and three lecturers. Findings: The participants were given knowledge about how to provide disaster education. Conclusion: To further strengthen teachers' abilities and skills in teaching about disasters, teachers were given training for 6 months via Zoom and for one week in Kitakyushu City to make teaching materials. Novelty/Originality of this Study: The novelty of this study lies in its implementation of disaster mitigation education for elementary school teachers in Mataram using traditional Japanese methods such as Machitanken and Kamishibai. This approach is unique as it integrates cultural techniques from Japan into the Indonesian educational context, aiming to enhance teachers' ability to educate students on disaster preparedness in a practical and engaging manner.